2008
DOI: 10.1177/1403494807088454
|View full text |Cite
|
Sign up to set email alerts
|

Area deprivation and trends in inequalities in self-rated health in Spain, 1987—2001

Abstract: Inequalities in self-rated health increased in Spain in this period. These inequalities may be explained by the social conditions existing throughout the period of reference, and the pattern varies according to gender, municipal area deprivation levels, and the individual indicator of social position used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 26 publications
3
8
0
1
Order By: Relevance
“…The close relationship with socioeconomic factors such as social condition or living in deprived areas has been described in previous studies. 8,10,11 It has also been shown in other international contexts 14,16,20,24 and was confi rmed in our multivariable models, where economic condition had a key role in explaining perceived health status.…”
Section: 17supporting
confidence: 87%
See 2 more Smart Citations
“…The close relationship with socioeconomic factors such as social condition or living in deprived areas has been described in previous studies. 8,10,11 It has also been shown in other international contexts 14,16,20,24 and was confi rmed in our multivariable models, where economic condition had a key role in explaining perceived health status.…”
Section: 17supporting
confidence: 87%
“…Many of these studies have shown a disadvantage of the south and northwest 1,4,8,11,26 in regard to mortality, health status and disability, among others. Regional differences have been seen in socioconomic and health indicators among the general population.…”
Section: Conclusõesmentioning
confidence: 99%
See 1 more Smart Citation
“…Neither could a modified Townsend Index of material deprivation, previously used in Spain, be used. 35 This index is based on each municipality's rates of unemployment, illiteracy, and private vehicles; data that were not all collected in the current study. Finally, as with every transversal study, it was not possible to establish a causal relationship between risk factors and social determinants.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…The country's National Health Surveys indicate that people residing in the municipal areas with the highest levels of deprivation are more likely to report worse self-rated health than those in the areas of lowest deprivation, and that the lower the level of education or occupational class, the greater the likelihood of lessthan-good health in all years studied. 35 Other findings, based on multilevel studies, seem to indicate that a person's health is determined both by their social position and by the socioeconomic characteristics of the setting in which they live. 33 Somewhat in line with this, the current study's data revealed a significant trend between the prevalence of cardiovascular risk factors and the level of education and employment status.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%